A proposed underlying source of human error. Issue 2 (3rd July 2017) - Williams, Jeremy C.
Abstract: Difficult tasks tend to increase response times and errors, but also, paradoxically, the more quickly we have to respond to something, the more likely it is that we will make an error. Although much-researched and discussed, the underlying reasons for these apparent connections and contradictions have never been satisfactorily explained. This paper proposes that cognitive information is processed in discrete packages so that, during decision making, the likelihood and type of error depends on the precise moment at which a decision is taken and the degree to which the decision is synchronous with package processing. By understanding how response times and error might be connected, we can make informed judgements about how one might affect the other. This offers the prospect of reducing human error, which is particularly important in safety critical environments, but which also has application for improving reliability across all human activity.